Boosting the CO2 reduction activity of Cu double-atom catalysts through coordination environment engineering - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Sustainable Energy & Fuels, 2025)
Double-atom catalysts (DACs) offer a reasonable and scalable route towards carbon neutrality owing to their efficient catalytic features. However, the challenges associated with the flexibility of their coordination structure usually restrict their full potential as efficient catalysts. Herein, we comprehensively examined the impact of coordination environment regulation on the CO2R activity of Cu2-DACs supported on C, N, or B co-doped graphene using ab initio simulations. We highlighted the marked role of the local coordination sphere of Cu2-DACs in modulating their structural stability and charge transfer characteristics, thereby regulating the adsorption of CO2 and various reaction characteristics. Notably, boron- and carbon-coordinated Cu2 centres (Cu2-BxCy) resulted in remarkably strong CO2 adsorption (-0.65 to -2.31 eV), attributed to their amplified electronic interactions with the CO2 molecule. The weak CO2 binding observed on the carbon-nitrogen- and nitrogen-boron-coordinated Cu2 centres (Cu2-NxCy and Cu2-NxBy) further highlighted the role of the coordination environment in facilitating the versatile binding modes of the key reaction species. The varying CO2 interactions in these systems were further comprehended and supported by a multilevel descriptor () combining both geometric and electronic parameters. This descriptor closely mirrored the DFT results, thereby accentuating its effectiveness as a predictive tool to perfectly model the CO2 interactions on these catalysts. Moreover, the dynamic behaviour in the adsorption modes led to partial breakdown of the conventional linear scaling relations between the key CO2 reduction intermediates (*COOH, *CO, and *HCO). Among the numerous types of investigated electrocatalysts, Cu2-B5C1 emerged as a highly active and selective catalyst for methanol production, with a remarkably low limiting potential of -0.54 V, surpassing the performance of several reported Cu-based systems. Besides, our findings underscored the often-overlooked yet crucial role of explicit solvation, which significantly altered both the potential-determining step and product selectivity. These outcomes emphasized the necessity of including solvation effects in realistic electrochemical modelling. Collectively, this study provides a critical mechanistic insight into better understanding the coordination effect on the CO2R and a robust design strategy for next-generation Cu-based DACs, guiding the development of highly efficient and selective catalysts for CO2 electroreduction.